Characterization, Preparation, and Purification of Marine Bioactive Peptides. (6th July 2017) - Wang, Xueqin; Yu, Huahua; Xing, Ronge; Li, Pengcheng
Abstract : Marine bioactive peptides, as a source of unique bioactive compounds, are the focus of current research. They exert various biological roles, some of the most crucial of which are antioxidant activity, antimicrobial activity, anticancer activity, antihypertensive activity, anti-inflammatory activity, and so forth, and specific characteristics of the bioactivities are described. This review also describes various manufacturing techniques for marine bioactive peptides using organic synthesis, microwave assisted extraction, chemical hydrolysis, and enzymes hydrolysis. Finally, purification of marine bioactive peptides is described, including gel or size exclusion chromatography, ion-exchange column chromatography, and reversed-phase high-performance liquid chromatography, which are aimed at finding a fast, simple, and effective method to obtain the target peptides.